(untitled) (Research, Society and Development, 2022)
Obesity is considered a disease characterized by the accumulation of fat in the body, this situation can trigger or even worsen morbidities such as diabetes, dyslipidemia and heart disease. In this sense, bariatric surgery is a technique used in medicine to promote weight reduction in individuals who have excess body fat, with or without associated comorbidities. The approach promotes a decrease in the rate of fat in the body, thus directly influencing the control of chronic diseases, especially type 2 diabetes mellitus (DM2), dyslipidemias and cardiovascular diseases, as the decrease in abdominal circumference impacts insulin sensitivity and process. of fatty acid and lipid oxidation, thus promoting a better quality of life for the patient. However, despite the surgical approach promoting several benefits to the individual, situations such as hypovitaminosis, due to the low absorption of nutrients, are evident and can strongly influence the patient’s quality of life. For this reason, the participation of a multidisciplinary team is essential in the follow-up, especially of the nurse, in view of their fundamental role in the orientation and elaboration of strategies that can promote the commitment and adherence of the patient to the treatment. Based on this, this study aims to clarify how bariatric surgery influences the individual’s metabolism as an alternative to control or even reverse the symptoms of comorbidities and show the influence of nurses in the process.